Studi kasus sistem penyaliran tambang batuabara pt bukit baiduri energi kabupaten kutai kartanegara provinsi kalimantan timur: - - Juan, Juan; Shalaho Dina Devy; Revia Oktaviani; Tommy Trides; Ardhan Ismail (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The mining system applied by PT Bukit Baiduri Energi is an open pit mining system utilizing the open-pit method. The application of the open-pit method creates a depression that has a high potential to become a catchment area for both surface runoff and groundwater. In the mining pit of PT Bukit Baiduri Energi, there is a sump located at an elevation of -86 meters above sea level (mdpl). The planned mining boundary is at an elevation of -110 mdpl. Therefore, this research aims to determine the area of the catchment, runoff discharge values, sump capacity, and pump capacity, so that the volume of incoming water can be known, allowing for the control of the sump to prevent overflow that could disrupt mining activities.. Based on the data obtained and the calculations performed, the catchment area was found to be 103.42 ha. In the calculation of runoff discharge using the rational method, the total runoff discharge entering sump A9 was found to be 4,211.66 m3/day. The capacity of the sump was measured at 125,187.62 m3. In the pump capacity calculation, the pump capacity based on the pumping discharge was found to be 2,926.80 m3/day.